2020
DOI: 10.1002/jcla.23431
|View full text |Cite
|
Sign up to set email alerts
|

MAGI2‐AS3 rs7783388 polymorphism contributes to colorectal cancer risk through altering the binding affinity of the transcription factor GR to the MAGI2‐AS3 promoter

Abstract: Background It has been indicated that the single nuclear polymorphisms (SNPs) in the long noncoding RNA (lncRNA) have association with colorectal cancer (CRC) susceptibility. Methods We enrolled 1078 cases with CRC and 1175 age‐ and gender‐matched cancer‐free controls to explore whether the polymorphisms in MAGI2‐AS3 have associations with CRC risk. qRT‐PCR, expression quantitative trait loci (eQTL) analyses, dual‐luciferase reporter assay, chromatin immunoprecipitation (ChIP), flow cytometry, and transwell as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Long non‐coding RNAs (lncRNAs) are an important class of ncRNAs that have a huge impact on the cancer progress. These RNAs are transcribed by RNA polymerase II, with a length of 200 nt or more, from different regions of the genome, including intronic and intergenic sites 5,6 . Considering this point, it has been inferred that lncRNA transcription usually does not depend on the presence of the open reading frames and it has been estimated that the human genome contains more than 15 000 lncRNAs‐related genes that could produce over 23 000 functional lncRNAs 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are an important class of ncRNAs that have a huge impact on the cancer progress. These RNAs are transcribed by RNA polymerase II, with a length of 200 nt or more, from different regions of the genome, including intronic and intergenic sites 5,6 . Considering this point, it has been inferred that lncRNA transcription usually does not depend on the presence of the open reading frames and it has been estimated that the human genome contains more than 15 000 lncRNAs‐related genes that could produce over 23 000 functional lncRNAs 7 .…”
Section: Introductionmentioning
confidence: 99%
“…All these studies report the downregulation of MAGI2-AS3 during carcinogenesis and support a role of this lncRNA as a tumor suppressor in adrenal, brain, breast, bladder, liver, lung, colorectal, prostate, pancreatic, ovarian, and renal cancers [ 208 , 209 , 210 , 213 , 214 , 217 , 220 , 222 , 223 , 230 , 232 , 234 , 235 , 236 , 237 , 238 , 239 ].…”
Section: Magi Cernas In Carcinogenesismentioning
confidence: 80%
“…A polymorphism in MAGI2-AS3 (rs7783388 GG genotype) seems to enhance colorectal cancer risk as a result of decreased binding affinity of glucocorticoid receptor to the MAGI2-AS3 promoter, leading to lower MAGI2-AS3 accumulation [ 236 ]. In this connection, functional experiments showed that MAGI2-AS3 overexpression suppressed proliferation (cell cycle arrest at G0/G1 phase), decreased migration and invasiveness, and promoted apoptosis of the human colon cancer SW480 and SW620 cell lines [ 236 ]. In this cancer, a MAGI2-AS3 LncRNA-miRNA-mRNA network of differentially expressed genes has been recently proposed [ 237 ].…”
Section: Magi Cernas In Carcinogenesismentioning
confidence: 99%
“…Additional suggestive signals were located in the MAGI2 gene and downstream of the IL15 gene. The SNP rs34931968 detected in our cohort is located in the MAGI2 gene, upstream of a lncRNA that is next to MAGI2 (called MAGI2-AS3 ), a lncRNA that has been involved in CRC [ 54 , 55 , 56 ]. In addition, the SNP rs34931968 is in linkage disequilibrium with an SNP (rs7783388) involved in CRC throughout changes in MAGI2-AS3 expression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs34931968 detected in our cohort is located in the MAGI2 gene, upstream of a lncRNA that is next to MAGI2 (called MAGI2-AS3 ), a lncRNA that has been involved in CRC [ 54 , 55 , 56 ]. In addition, the SNP rs34931968 is in linkage disequilibrium with an SNP (rs7783388) involved in CRC throughout changes in MAGI2-AS3 expression [ 56 ]. In the case of IL15 , its expression has been associated with the outcome of CRC [ 57 ].…”
Section: Discussionmentioning
confidence: 99%